IoT based Coma Patient Monitoring System using wearable sensors - Lokesh B, A Angulakshmi, Ashwini Kumari P, Manojkumar Sinde, Lokesh M (International Journal of Advanced Science and Technology, 2020)
Coma can be classified into two stages vegetative state (VS) and minimally conscious state (MCS). In VS there are no signs of consciousness which is in contrast to that of MCS. The record of the comatose transition from VS to MCS is not effectively sustained. In the present hospital, a caretaker is mandatorily needed to supervise the patient continuously. Such methods of supervision have a greater threat due to human errors. This impact can be surpassed by following the proposed system which focuses on monitoring and alerting the caretaker about the transition from VS to MCS, continuously monitor the vitals such as heartbeat, pulse rate using relative biometric sensors of comatose, monitor the physiological signals to understand the patients emotional status, and change in behavioral approach for speeding up the healing process by unifying the wireless sensors to ESP8266 NodeMCU microcontroller board. The proposed system continues its functionality even after gaining consciousness in analyzing each body part on their muscle activity level and establishing mobile-network with a well-known sensor integration platform. The system is beneficial in reducing the burden of a manual requirement to continuously monitor the comatose along with assistance to the doctor about the health and consciousness status of the comatose remotely through the use of a mobile application. It alerts the doctor of any abnormal conditions in the vitals of the comatose. The proposed system also cares about data analysis for future reference.